2010
DOI: 10.1007/s10750-010-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mortality of Arctic charr and European whitefish reared at low temperatures

Abstract: This comparative study explores how low temperatures affect the mortality and growth of first generation hatchery-reared progeny of subarctic populations of Arctic charr (Salvelinus alpinus L.) and European whitefish (Coregonus lavaretus L.). Replicate fish groups where held under simulated natural light regimes (70°N) at three constant temperatures (1, 3 and 6°C). The mortality of Arctic charr was low (B1.4%) at all temperature treatments, whereas the mortality of whitefish increased with decreasing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…As in sympatry with brown trout , Arctic charr seem to be competitively dominant over whitefish in cold, oligotrophic high-altitude lakes 30 with elongated ice-cover period and limited pelagic production. This assumption is supported by recent laboratory experiments showing a higher survival and growth rate for Arctic charr reared at low temperatures (Siikavuopio et al 2010), but also by present field data from Gaesjavri, where Arctic charr made around 65 % of the total fish catch (Appendix A in IV) and also had a more pelagic trophic niche than whitefish ( Fig. 2 in IV).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…As in sympatry with brown trout , Arctic charr seem to be competitively dominant over whitefish in cold, oligotrophic high-altitude lakes 30 with elongated ice-cover period and limited pelagic production. This assumption is supported by recent laboratory experiments showing a higher survival and growth rate for Arctic charr reared at low temperatures (Siikavuopio et al 2010), but also by present field data from Gaesjavri, where Arctic charr made around 65 % of the total fish catch (Appendix A in IV) and also had a more pelagic trophic niche than whitefish ( Fig. 2 in IV).…”
supporting
confidence: 75%
“…The long annual ice-cover period and limited pelagic production in Gaesjavri probably reduce the abundance and growth of whitefish, but at the same time promote the competitive dominance of Arctic charr with superior ability to feed in cold and dark conditions (e.g. Siikavuopio et al 2010. Recent field data from Kilpisjärvi also demonstrates that large piscivorous Arctic charr can prey upon small pelagic whitefish throughout the winter (K.K.…”
mentioning
confidence: 99%
“…Arctic charr are found at higher latitudes than any other freshwater fish species and are therefore the species most likely to exhibit specific adaptations for surviving under conditions where winters are long and productivity is low. Laboratory studies of charr have found them capable of growing at very low temperatures (*2-5°C : Larsson et al 2005) while field and laboratory studies have shown that they feed throughout long periods of ice-cover (Klemetsen et al 2003;Svenning and Klemetsen 2007;Amundsen and Knudsen 2009) and can exhibit over-winter growth (Siikavuopio et al 2010). Size classes that have grown large enough to switch their diet from zooplankton to benthic invertebrates may feed better over winter since winter abundance of benthic invertebrates can be much greater than zooplankton abundance (Byström et al 2006;Hölker 2006).…”
Section: Specialization Survival Strategiesmentioning
confidence: 99%
“…Glucose concentrations between c.a 2 and 5.5 mmol dm -3 were reported for the species by Lappivara (2001) and Siikavuopio et al (2010). Brzuzan et al (2009) reported values of glucose between 3.4 and 9.02 mmol dm -3 , and Ernst et al (2006) between 0.87 and 3.0 mmol dm -3 .…”
Section: Discussionmentioning
confidence: 81%
“…0.38 in whitefish reared in 13.0±0.5°C and pH 7.5±0.25. Siikavuopio et al (2010) found 0.32, 0.31 and 0.28 PCV in fish reared in 1, 3 and 6°C respectively (pH 7.2). We suppose that higher PCV resulted from acclimation to environmental conditions.…”
Section: Discussionmentioning
confidence: 85%